2018
DOI: 10.1007/s11999.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Cerebrovascular Events Are Associated With Nontraumatic Osteonecrosis of the Femoral Head

Abstract: Level III, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The underlying mechanism is thought to be related to the endothelial dysfunction. In the former study [14], the ONFH patients were found to have about twice increased risk for MACCE even after multivariate adjustment for medications, surgery and relevant comorbidities. The latter study was aimed to find the incidence of unprovoked VTE in non-traumatic ONFH [20].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The underlying mechanism is thought to be related to the endothelial dysfunction. In the former study [14], the ONFH patients were found to have about twice increased risk for MACCE even after multivariate adjustment for medications, surgery and relevant comorbidities. The latter study was aimed to find the incidence of unprovoked VTE in non-traumatic ONFH [20].…”
Section: Discussionmentioning
confidence: 90%
“…Short-term or long-term administration of NSAID protected ONFH patients from postoperative VTE was noted in the present study. Also, data from the previous two studies [14,20] have documented that NSAID has the protective effects against not only provoked VTE but also MACCE in patients with nontraumatic ONFH. Although most early researches have shown the use of non-selective NSAID strongly leads to endothelial dysfunction and links to arterial/venous thrombotic complications [27,28], yet more and more recent meta-analyses have challenged the cardiovascular safety issue of NSAID, especially cyclooxygenase-2 (COX-2) selective inhibitor [29,30].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the mechanism leading to these metabolic changes as a result of the viral infection remains unknown. Osteonecrosis is independently associated with an increased risk of adverse CV outcomes in SARS patients treated with corticosteroids and warrants further exploration [98,99]. Psychiatric morbidities, including chronic fatigue syndrome, were also reported in patients who recovered from SARS [100].…”
Section: Future Complications and Implicationsmentioning
confidence: 99%